Occurrence, Bioaccumulation, and Human Exposure Risk of the Antiandrogenic Fluorescent Dye 7-(Dimethylamino)-4-methylcoumarin and 7-(Diethylamino)-4-methylcoumarin in the Dongjiang River Basin, South China - Yufeng Lai; Yin Huang; Danlin Yang; Jingchuan Xue; Runlin Chen; Rundong Peng; Siying Zhang; Yufei Li; Guochun Yang; Yuxian Liu (Toxics)
Recently, 7-diethylamino-4-methylcoumarin (DEAMC) has been identified as a potent antiandrogenic compound in the surface water; however, little is known about the antiandrogenic potentials of other synthetic coumarins and their occurrence in the aquatic ecosystem. In this study, for the first time, we observed that 7-dimethylamino-4-methylcoumarin (DAMC) elicited androgen receptor (AR) antagonistic activity with a 50% inhibitory concentration (IC50) of 1.46 µM, which is 14.3 times more potent than that observed for DEAMC (IC50 = 20.92 µM). We further collected abiotic (water and sediment) and biotic (plant, plankton, and fish) samples (n = 208) from a subtropical freshwater ecosystem, the Dongjiang River basin, in southern China, and determined the concentrations of the two coumarins in these samples. Overall, DAMC was the predominant compound found in the sediment, plant, algae, zooplankton, and fish muscle samples, with median concentrations at 0.189, 0.421, 0.832, 0.798, and 0.335 ng/g dry wt. (DW), respectively, although it was not detected in any surface water sample. For DEAMC, the median concentrations observed in the surface water, sediment, plant, algae, zooplankton, and fish muscle samples were 0.105 ng/L, 0.012, 0.051, 0.009, 0.008, and 0.181 ng/g DW, respectively. The bioaccumulation factor (BAF) values of DAMC and DEAMC in the algae, zooplankton, and fish muscle exceeded 5000 L/kg, suggesting that the two coumarins may have significant bioaccumulation potentials in aquatic biota. Additionally, the mean daily intake (EDI) of coumarins through fish consumption was estimated as 0.19 ng/kg BW/day for male toddlers. This is the first field study to illustrate the antiandrogenic potential of DAMC and document the widespread occurrence of the two synthetic coumarins in aquatic ecosystems.